POTENTIAL FOR DEVELOPMENT OF RURAL TOURISM IN DOLNA PRESPA (Innovation in Woodworking Industry and Engineering design, 2026)
The motive for such a study was the valorization and categorization of architectural heritage in some rural areas in Macedonia that are located close to larger urban areas and the possibility of sustainable spatial development as well as the promotion of rural areas through action in areas such as architecture, urbanism, spatial planning, environmental protection, development of the civil sector and development of rural tourism. For this purpose, we analyzed three rural entities and villages in the Prespa region. We selected the locations because they are located close to larger town centers such as Resen and Bitola and the border with R. Greece and this is the potential for development of rural tourism.